2020
DOI: 10.1680/jmacr.18.00563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bond property of longitudinal bars on seismic behaviour of reinforced-concrete columns

Abstract: Four circular fly-ash concrete columns reinforced by steel rebars with different bond levels were tested to investigate the influence of bond strength of longitudinal steel rebar on the seismic behaviours of reinforced-concrete (RC) members. Furthermore, a fibre-element method considering steel bond slip was used to investigate the influence of bond properties of steel rebar on seismic responses of circular RC columns, with the test results used to validate reasonability. The comparison of results shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The authors have theoretically analysed the influence of the bond strength of longitudinal reinforcement on the seismic behaviours of RC columns. The results indicated that a decrease in the bond strength can substantially improve the ductility of RC columns and that the yield process can be delayed such that the longitudinal reinforcement can be maintained in the elastic region (Wang and Sun 2020a;Wang and Sun 2020b). Based on the above theoretical foundation, the authors proposed the use of lowbond high-strength reinforcement (LBHSR) as the tensile longitudinal rebar of RC columns.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have theoretically analysed the influence of the bond strength of longitudinal reinforcement on the seismic behaviours of RC columns. The results indicated that a decrease in the bond strength can substantially improve the ductility of RC columns and that the yield process can be delayed such that the longitudinal reinforcement can be maintained in the elastic region (Wang and Sun 2020a;Wang and Sun 2020b). Based on the above theoretical foundation, the authors proposed the use of lowbond high-strength reinforcement (LBHSR) as the tensile longitudinal rebar of RC columns.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to developing SC-RC column using a simple and low-cost technology is worthy of attention. Wang and Sun [11] theoretically analyzed the seismic behaviors of RC columns reinforced by steel rebars with different bond strengths and found that a decrease in the bond strength of the longitudinal rebar delayed the yielding process, such that longitudinal reinforcement within the elastic region can provide a more durable SC force to the entire RC column. Wang et al [12,13] found experimentally that the seismic damage was slighter and the residual deformation was smaller when the RC columns were reinforced by a debonded high-strength rebar (DHSR) and a low-bond high-strength rebar (LBHSR), compared to RC columns with normal steel rebars.…”
mentioning
confidence: 99%